Psoriasiform dermatoses: Microscopic approach - Rajalakshmi Tirumalae (Wolters Kluwer Medknow Publications, 2013)
Psoriasiform dermatoses often pose challenges to both dermatologists and pathologists alike. With proper clinicopathologic correlation and a systematic approach, it is possible to arrive at a specific diagnosis in most cases. This article attempts to outline a practical, step-wise method of looking at these cases and highlights some important clues in individual conditions.